Pendampingan dan Pelatihan Simulasi Bantuan Hidup Dasar di SMK Kesehatan TRIS'S Maros - Saputra, M. Khalid Fredy; Djunaedi, Djunaedi; Ambarwati, Eny Retna; Ansar, Ansar; Noor, Mohammad Arifin; Dunggio, Abdul Rivai Saleh; Rahmat, Rezqiqah Aulia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Basic life support is the initial treatment for victims of cardiac arrest and respiratory arrest. Basic life support includes several skills, namely recognizing sudden cardiac arrest, asking for help immediately, performing cardiopulmonary resuscitation, and even in some countries the use of AED (Automatic External Defibrillator) has been introduced. This community service activity aims to improve the ability of Tri's Maros Health Vocational School students to simulate the implementation of basic life support. Participants who took part in this activity were very enthusiastic about participating in the simulation activity of implementing basic life support. The results of community service activities show that the majority of students' knowledge before carrying out the basic life support simulation is poor, after carrying out the basic life support simulation the majority of their knowledge is good, the majority of students' skills before carrying out the basic life support simulation are lacking. It is hoped that the management of Tri's Maros Health Vocational School will carry out regular basic life support training plans, provide tools and materials such as CPR pantoms for babies, children and adults for students to use to practice basic life support actions in order to increase students' knowledge in providing basic life support to patients in emergency conditions.